1988
DOI: 10.6028/nist.ir.88-3852
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and fate of tributyltin species in microbial biofilms

Abstract: Microbial biofilms, composed of microorganisms originally obtained from estuarine harbor-exposed commercial organotin-painted panels, accumulated tributyltin (TBT) spiked into estuarine water.Both algal or bacterial-dominated biofilms were grown by varying nutrient conditions and were found to accumulate TBT in excess of 300 ng/mg biomass (dry weight basis) from estuarine water solutions containing 50 ^g/L TBT, corresponding to bioconcentration factors of over 7000. No degradation of TBT to dibutyltin (DBT) sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…TBT þ release rate studies. The diffusion resistance/ trapping ability of biofilms was also confirmed by Blair et al (1988) and Schatzberg (1996) who reported a high degree of accumulation of TBT species within the biofilm matrix (bioconcentration factors 47000). As a direct consequence of this accumulation, a reduction in the release rate of the TBT moieties is expected (as observed by Mihm & Loeb, 1988) although, again, the shift from a bacterial to an algal biofilm led to contradictory results (see Figure 5).…”
Section: Potential Sources Of Interference Biofilm-af Paint Mechanismssupporting
confidence: 58%
See 1 more Smart Citation
“…TBT þ release rate studies. The diffusion resistance/ trapping ability of biofilms was also confirmed by Blair et al (1988) and Schatzberg (1996) who reported a high degree of accumulation of TBT species within the biofilm matrix (bioconcentration factors 47000). As a direct consequence of this accumulation, a reduction in the release rate of the TBT moieties is expected (as observed by Mihm & Loeb, 1988) although, again, the shift from a bacterial to an algal biofilm led to contradictory results (see Figure 5).…”
Section: Potential Sources Of Interference Biofilm-af Paint Mechanismssupporting
confidence: 58%
“…copper and TBT-based compounds) is rapidly covered by a microbial biofilm (Saroyan, 1969;Bishop et al 1974;Loeb, 1980;Dempsey, 1981a;1981b;Jackson & Jones, 1988;Blair et al 1988;Mihm & Loeb, 1988;Heath et al 1993;Schatzberg, 1996;White et al 34 D. M. Yebra et al 1996;1999;Tang & Cooney, 1998;Woods et al 1988;Cooney & Tang, 1999;Valkirs et al 2003). Some examples of fouling sequences on AF paints are given by Jackson and Jones (1988).…”
Section: Biofilms On Af Paintsmentioning
confidence: 96%
“…Based on these data, it is estimated that TBTs are absorbed or bioconcentrated by bacteria (Blair et al 1988), phytoplankton (Laughlin et al 1986), mollusks (Waldock et al 1983), crustacean species (Evans et al 1984), and fish (Short andThrower 1986, Davies et al 1987). The few data currently available on the bioconcentration of tin and derived products is exclusively devoted to TBT; this reflects the widespread use of TBT as a biocide in marine antifoulants on the one hand, and the recent development of butyltin-specific analytical techniques on the other hand.…”
Section: Contamination Of Food and Living Organismsmentioning
confidence: 99%